Five different cases of ectopic testes in children: a self-experience with literature review. Issue 3 (28th October 2019) - Joda, Ali Egab
Abstract : Background: Empty scrotum may be due to many reasons; besides true undescended testis these are monorchia, retractile testis, atrophy of testis due to torsion and ectopic testis. The location of testis in an aberrant site after passing through the inguinal canal and leaving it via external ring is a condition called ectopic testis. The most common aberrant locations of ectopic testes are superficial inguinal pouch (Denis Browne pouch), within anterior abdominal wall, perineum, femoral canal, contralateral scrotum (transverse testicular ectopia) and prepenile area. Methods: Description of management of five different cases of ectopic testes over a period of 10 years' experience in pediatric surgery have been done with review of the literature about this rarity. Results: Five different cases of ectopic testes were as follows: infants 3 months of age with right ectopic testis in anterior abdominal wall near anterior superior iliac spine, 4 months of age with left perineal testis, 6 months of age with an ectopic femoral testis on left side, 8 months of age with transverse testicular ectopia on left side and 10 months of age with right true undescended testis and left perineal testis. Conclusions: Search for ectopic sites of testes should always be in mind during examination of patients with empty scrotum. Early surgical repair of ectopic testes is recommended, as there is no chance of spontaneous correction to the normal location. Long-term follow-up is necessary due to relatively high incidence of infertility and malignant transformation. Surgeons should be aware of the rare possibility of transverse testicular ectopia in cases of inguinal hernia with impalpable testis on the contralateral side.